The take over the word: A counter-history of the Spanish Transition from Numax presents… (1980) by Joaquim Jordà to The Year of Discovery (2020) by Luis López Carrasco - Rubio López, Cristina (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This article aims to determine if there is continuity between the films Numax presents... (1980) and The Year of Discovery (2020). If the cinema of Luis López Carrasco refers to Joaquim Jordà’s one and, inversely, if Jordà's is projected onto that of López Carrasco. And if, in addition to sharing a diagnosis of the democratic transition and the industrial reconversion that went through it, they do not also share an artistic tradition: if the cinema of both does not connect with that urgent, peripheral and committed documentary that was deployed during that same historical period they portray in their films.